TRANSFORMASI SDN WEDORO II MENUJU ZONA BEBAS BULLYING MELALUI PENDEKATAN SEKOLAH RAMAH ANAK - Khurliyah, Fira; Mardhatillah, Mardhatillah; Suciptaningsih, Oktaviani Adhi (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to identify and analyze the transformation of SDN Wedoro II into a bullying-free zone through the Child-Friendly School approach. The research method used is qualitative with a case study approach. The research subjects consisted of 89 students, 12 teachers and staff, and 30 parents at SDN Wedoro II. Data collection tools included interviews, observations, and questionnaires. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the implementation of the Child-Friendly School approach has significantly contributed to reducing bullying cases at the school. There has been an increased awareness of the importance of a safe and comfortable environment for all students. In addition, the active participation of all parties, including parents, in school programs has proven effective in fostering a positive school culture. Thus, the transformation of SDN Wedoro II into a bullying-free zone can serve as a reference for other schools in their efforts to create a better educational environment.